Analyzing Maternal Needs for “Internet+ Nursing Service” After Hospital Discharge: A SERVQUAL-KANO Model Approach - Ding L; Ding Y; Wang Y; Li X; Liu Y (Journal of Multidisciplinary Healthcare)
Lei Ding,1,2,* Yajie Ding,2,* Yiting Wang,1,2 Xianwen Li,1 Ying Liu2 1School of Nursing, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 2Department of Obstetrics, Women’s Hospital of Nanjing Medical University (Nanjing Women and Children’s Healthcare Hospital), Nanjing, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xianwen Li, School of Nursing, Nanjing Medical University, 101 Longmian Avenue, Nanjing, Jiangsu, 211166, People’s Republic of China, Email xwli0201@njmu.edu.cn Ying Liu, Department of Obstetrics, Women’s Hospital of Nanjing Medical University (Nanjing Women and Children’s Healthcare Hospital), Nanjing, Jiangsu, 210004, People’s Republic of China, Email 371768109@qq.comPurpose: The provision of postnatal continuity of care is of significant importance to new mothers. Given the prevalence of “Internet+ Nursing Services”, there has been a paucity of research exploring the internet-based home care needs of mothers following their discharge from hospital. This study employs a combination of the SERVQUAL and KANO models to investigate maternal requirements for Internet+ nursing services and to establish a foundation for enhancing the quality of postnatal nursing services.Patients and Methods: A questionnaire was designed by combining SERVQUAL and KANO models, and a cross-sectional survey was conducted in the obstetrics department of a tertiary hospital in China after expert correspondence. The survey targeted 279 mothers about to be discharged after delivery, aiming to explore their demand for Internet+ nursing services post-discharge. Data were analyzed according to the KANO model.Results: The better values (satisfaction coefficient) of Internet+ nursing services ranged from 42.91% to 78.46%, while the worse values (dissatisfaction coefficient) were 28.91% to 63.20%. The must-be and one-dimensional need attributes of maternity are mainly tangibility, reliability, responsiveness, and assurance dimensions, and empathy and economy are attractive attributes. Two items within the tangibles dimension, namely ease of operation of the platform and nurses’ dress code, were deemed to be indifferent attributes. In the quadrant analysis diagram, the attributes of must-be, one-dimensional, attractive, and indifferent were 8(33.3%), 66(25.0%), 8(33.3%), and 2(8.3%), respectively.Conclusion: Attributes of Chinese mothers’ needs for Internet+ nursing services after hospital discharge were defined, ranked, and categorized by the KANO model, providing a theoretical basis for the targeted design and improvement of care services. It is suggested that care managers consolidate must-be attributes and one-dimensional attributes, optimize attractive attributes, and transform indifferent attributes to better meet the multifaceted service needs of mothers.Keywords: maternal, service needs, KANO model, SERVQUAL model, internet+ nursing service